Experimental Study on the Adsorption Performance of Metal–Organic Framework MIL-101 (Cr) for Indoor Toluene - Zirong Zhao; Jinzhe Nie; Honghao Huang; Fuqun He; Kaiqiao Wang; Pu Yang (Buildings)
In this study, MIL-101 (Cr) was synthesized and characterized in terms of its physical properties. The adsorption breakthrough curves for toluene were measured and compared to those of conventional adsorbents (i.e., silica gel and activated carbon) at typical indoor concentrations of toluene. The results show that MIL-101 (Cr) exhibits a 5–8 times higher adsorption capacity for toluene compared to silica gel at low concentrations. The adsorption isotherm of MIL-101 (Cr) for toluene conforms to the Langmuir model. Increasing temperature reduces the adsorption breakthrough time and saturation time, but it leads to a significant decrease in the adsorption capacity. During the breakthrough experiment, flow rate had little effect on adsorption capacity, but higher flow rates notably decreased the breakthrough and saturation times. The negative values of ΔG, ΔH, and ΔS indicate that the adsorption of toluene on MIL-101 (Cr) is a spontaneous and exothermic process. Compared to traditional adsorbents, MIL-101 (Cr) exhibits desirable performance in toluene adsorption in indoor environments. It shows significant potential for indoor air purification applications.